XD Metrics on Demand Value Analytics: Visualizing the Impact of Internal Information Technology Investments on External Funding, Publications, and Collaboration Networks - Scrivner, Olga; Singh, Gagandeep; Bouchard, Sara E.; Hutcheson, Scott C.; Fulton, Ben; Link, Matthew R.; Börner, Katy (Frontiers in Research Metrics and Analytics, 2018)
Many universities invest substantial resources in the design, deployment, and maintenance of campus-based cyberinfrastructure. To justify the expense, it is important that university administrators and others understand and communicate the value of these internal investments in terms of scholarly impact as measured by external funding, publications, and research collaborations. This paper introduces two visualizations and their usage in the Value Analytics (VA) module for Open XD Metrics on Demand (XDMoD). The VA module was developed by Indiana University’s (IU) Research Technologies division in conjunction with IU’s Cyberinfrastructure for Network Science Center (CNS) and the University at Buffalo’s Center for Computational Research (CCR). It interrelates quantitative measures of information technology (IT) usage, external funding, and publications in support of IT strategic decision making. This paper details the data, analysis workflows, and visual mappings used in the two VA visualizations that aim to communicate the value of different IT usage in terms of NSF and NIH funding, resulting publications, and associated research collaborations. To illustrate the feasibility of measuring IT values on research, we measured its financial and academic impact from the period between 2012 and 2017. The financial return on investment (ROI) is measured in terms of the funding, totaling $ 21,016,055 for NIH and NSF projects, and the academic ROI constitutes 1,531 NIH and NSF awards and 968 publications associated with 83 NSF and NIH awards. In addition, the results show that Medical Specialties, Brain Research, and Infectious Diseases are the top three scientific disciplines ranked by their publication records during the given time period.